Computer assisted design of transducers for ultrasonic sensor systems - Henning, Bernd; Rautenberg, Jens; Unverzagt, Carsten; Schröder, Andreas; Olfert, Sergei (Journal of Measurement Science and Technology, MST)
In this contribution, possibilities and methods for computer-assisted design of ultrasound transducers are described. These transducers are essential for an ultrasonic sensor design, e.g. for continuous non-invasive determination of quantities that are important in process technology. To achieve technical reliability and robustness, the precise determination of all acoustic properties of the used sensor materials is of great importance. Problem-oriented modeling, numerical simulation, special optimization algorithms and improved methods for the visualization of propagating waves offer new and promising possibilities for developing ultrasonic transducers with enhanced properties.